Evaluation of print angle on accuracy of 3D printed dental models - Aarthi Chand; Hashmi K. M; K. Saidath (Frontiers in Dental Medicine, 2026)
Introduction Additive manufacturing, introduced by Charles Hull through stereolithography, enables the fabrication of three-dimensional (3D) structures with high precision by curing material layer by layer. In dentistry, print orientation significantly influences the dimensional accuracy and mechanical properties of 3D-printed models used for surgical splints, aligners, drill guides, and other orthodontic applications. This study evaluated the effect of different print orientations on the dimensional accuracy of maxillary and mandibular dental models fabricated using a Digital Light Processing (DLP) printer. Aim and objective To evaluate the effect of different 3D printing angles on the dimensional accuracy of dental models fabricated using a Digital Light Processing (DLP) printer. Materials and methods Type IV gypsum dental casts were scanned using the 3Shape OrthoAnalyzer and printed at four orientations (0°, 30°, 60°, and 90°) using a DLP printer. The printed models were washed, post-cured, rescanned, and digitally superimposed onto the original scans to assess dimensional accuracy. Statistical analysis was performed using ANOVA followed by Tukey's post hoc test, with a significance level of p < 0.05. Results Print orientation significantly affected the dimensional accuracy of maxillary models, with significant differences observed among selected orientation groups. No significant differences were found among mandibular models printed at different orientations. Significant differences were also observed between maxillary and mandibular models printed at 30° and 60°. Conclusion Maxillary models printed at 30° and 60° demonstrated greater dimensional accuracy than those printed at 0° and 90°. Although print orientation influenced accuracy, all deviations were within clinically acceptable limits, indicating that orientation may be selected based on clinical requirements, printing time, resin usage, and build platform efficiency.